The dental identification of victims of an aircraft accident in Malaysia - Nambiar, P.; Jalil, N.; Singh, B. (Wiley, 1997)
On 15 September 1995 a Malaysian Airlines (MAS) Fokker 50 plane plunged while descending and crashed, killing thirty-four passengers aboard. The dental disaster victim identification team comprising dental surgeons from the Dental faculty, University of Malaya; Ministry of Health, Sabah; and the Malaysian Defence Forces played an active role in the identification process. Most of the bodies were badly mutilated, disfigured and severely incinerated. Problems were encountered due to inadequate facilities and space at the mortuary. Difficulties were also encountered during the procurement and deciphering of information from dental records. This disaster has however created greater awareness amongst Malaysians of the important role of forensic odontology in mass disasters.